Underdeveloped region education: teacher existance, access and educational policy - MAGAYANG, D; KOMARIAH, A; GAFFAR, M.F; SUHARDAN, D; MEIRAWAN, D; KURNIADY, D.A (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article aims to (1) describe the complexity of Education implementation in an underdeveloped region in Yahukimo Papua as seen from the teacher and (2) analyze education policies to solve the problem of lack of teachers. This research used qualitative methods by conducting in-depth-interview, observation, documentation and focus group discussions. The results show that fewer teachers and difficult access to school location are the cause of complexity in Education problems, particularly in the normalization of the learning process. Such condition is worsened by the inability to implement educational policy for underdeveloped regions that cant guarantee teacher availability and other educational personnel.